RELATIONSHIP BETWEEN EXPOSURE TO CIGARETTE SMOKE AND AGE OF FIRST CHILD WITH BREAST CANCER AT A HOSPITAL IN METRO CITY - Anggun Anisyabilla; Sadiman Sadiman; Yoga Triwijayanti (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
Breast cancer is the most common type of cancer in women worldwide, including in Indonesia. It occurs due to uncontrolled cell growth in breast tissue, which damages surrounding tissue and spreads to other organs. WHO data from 2022 indicates that 2.3 million women were diagnosed with breast cancer and 670,000 died. The exact cause is unknown, but it often occurs in the milk ducts or lobules. Impacts include physical, mental, and emotional conditions. The purpose of this study was to identify the association between household cigarette smoke exposure and age at first pregnancy with breast cancer in the Oncology Surgery Unit of General Ahmad Yani General Hospital, Metro. This quantitative study used a case-control study design, conducted in the Oncology Surgery Unit of a hospital in Metro City. A sample of 82 women was selected using a consecutive sampling technique, consisting of 41 women with breast cancer and 41 women without breast cancer. Data were collected through interviews and review of necessary medical records using a questionnaire. Data analysis used the chi-square test with a 95% confidence level (α = 0.05). The results showed that 31.7% of adult women in the case group had a history of cigarette smoke exposure at home for >26 years. Forty-one percent of adult women in the case group had their first pregnancy aged >35 years. Statistical tests showed a significant association between cigarette smoke exposure and breast cancer incidence (p = 0.004 and OR = 9.054). Age at first pregnancy >35 years was also significantly associated with breast cancer incidence (p = 0.002; OR = 6.552). The study concluded that there is a significant association between cigarette smoke exposure and age at first pregnancy >35 years and breast cancer incidence. Breast cancer prevention is important by implementing smoke-free areas at the household level and avoiding pregnancy at risk through education.